Risk of Autoimmune Diseases Following Optic Neuritis: A Nationwide Population-Based Cohort Study - Ma, Kevin Sheng-Kai; Lee, Chee-Ming; Chen, Po-Hung; Yang, Yan; Dong, Yi Wei; Wang, Yu-Hsun; Wei, James Cheng-Chung; Zheng, Wen Jie (Frontiers in Medicine, 2022)
Objectives: Optic neuritis (ON) is believed to be an immune-mediated disease; however, the association between ON and autoimmune diseases remains unclear. This study aimed to identify the incidence rate and hazard ratio (HR) of autoimmune diseases in patients with ON. Methods: This nationwide, population-based, retrospective cohort study collected patients’ data between 1999 and 2013 from the National Health Insurance Research Database in Taiwan. A total of 9,235 patients were included. Using 1:4 propensity scoring, 1,847 patients were enrolled in the ON group and 7,388 in the non-ON group according to age, sex, comorbidities, and corticosteroid use. Follow-up was started from the index date and the endpoint was a new diagnosis of autoimmune diseases, specifically, myasthenia gravis (MG), psoriatic arthritis (PsA), systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and ankylosing spondylitis (AS). Results: The Kaplan-Meier curves of the cumulative incidence of autoimmune diseases indicated that patients with ON had a higher risk of developing autoimmune diseases than patients without ON. In addition, the Cox proportional hazard regression showed that patients with ON had a higher HR (adjusted HR, 1.40; 95% CI, 1.05–1.87) of autoimmune diseases compared to those without ON. Furthermore, patients with ON aged <65 years (adjusted HR: 2.13, 95% C.I.: 1.14–3.96), who were female (adjusted HR: 0.7, 95% C.I.: 0.54–0.90), and with chronic liver disease (adjusted HR: 1.73, 95% C.I: 0.42–4.17) had a significantly increased risk of autoimmune diseases compared to patients without ON with the same characteristics. Conclusions: Patients with ON were found to have a higher risk of developing autoimmune diseases, especially in young and middle-aged females. clinicians should consider this association in managing patients with ON.